\dfrac{-24}{x}=\dfrac{-30}{-35}
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{3}{6}=\dfrac{3:3}{6:3}=\dfrac{1}{2}\\ \dfrac{18}{24}=\dfrac{18:6}{24:6}=\dfrac{3}{4}\\ \dfrac{5}{35}=\dfrac{5:5}{35:5}=\dfrac{1}{7}\\ \dfrac{40}{90}=\dfrac{40:10}{90:10}=\dfrac{4}{9}\\ \dfrac{75}{30}=\dfrac{75:15}{30:15}=\dfrac{5}{2}\)
\(\dfrac{3}{6}=\dfrac{3:3}{6:3}=\dfrac{1}{2}\\ \dfrac{18}{24}=\dfrac{18:6}{24:6}=\dfrac{3}{4}\\ \dfrac{5}{35}=\dfrac{5:5}{35:5}=\dfrac{1}{7}\\ \dfrac{40}{90}=\dfrac{40:10}{90:10}=\dfrac{4}{9}\\ \dfrac{75}{30}=\dfrac{75:15}{30:15}=\dfrac{5}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\dfrac{-15}{17}=-1+\dfrac{2}{17}\\ -\dfrac{19}{21}=-1+\dfrac{2}{21}\\ Vì:\dfrac{2}{17}>\dfrac{2}{21}\Rightarrow-1+\dfrac{2}{17}>-1+\dfrac{2}{21}\Rightarrow-\dfrac{15}{17}>-\dfrac{19}{21}\\ b,-\dfrac{24}{35}=-1+\dfrac{11}{35};-\dfrac{19}{30}=-1+\dfrac{11}{30}\\ Vì:\dfrac{11}{35}< \dfrac{11}{30}\Rightarrow-1+\dfrac{11}{35}< -1+\dfrac{11}{30}\\ \Rightarrow-\dfrac{24}{35}< -\dfrac{19}{30}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(\Leftrightarrow\dfrac{16}{x}=\dfrac{-4}{5}\)
hay x=-20
b: =>x+7=-10
hay x=-17
Tìm số nguyên x, biết:
a) \(\dfrac{-28}{35}=\dfrac{16}{x};\) b) \(\dfrac{x+7}{15}=\dfrac{-24}{36}.\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a.\)
\(\dfrac{-28}{35}=\dfrac{16}{x}\)
\(\Rightarrow x=\dfrac{35\cdot16}{-28}=\dfrac{5\cdot7\cdot4\cdot4}{-7\cdot4}=-20\)
\(b.\)
\(\dfrac{x+7}{15}=\dfrac{-24}{36}\)
\(\Rightarrow x+7=\dfrac{15\cdot-24}{36}=\dfrac{5\cdot3\cdot-12\cdot2}{12\cdot3}=-10\)
\(\Leftrightarrow x=-17\)
![](https://rs.olm.vn/images/avt/0.png?1311)
24:
\(\Leftrightarrow\dfrac{1}{\left(x+2\right)\left(x+3\right)}+\dfrac{1}{\left(x+3\right)\left(x+4\right)}+\dfrac{1}{\left(x+4\right)\left(x+5\right)}+\dfrac{1}{\left(x+5\right)\left(x+6\right)}=\dfrac{1}{8}\)
\(\Leftrightarrow\dfrac{1}{x+2}-\dfrac{1}{x+6}=\dfrac{1}{8}\)
\(\Leftrightarrow\left(x+2\right)\left(x+6\right)=8\left(x+6\right)-8\left(x+2\right)\)
\(\Leftrightarrow x^2+8x+12=8x+48-8x-16=32\)
=>(x+10)(x-2)=0
=>x=-10 hoặc x=2
25: \(\Leftrightarrow\dfrac{\left(x+1\right)^2+1}{x+1}+\dfrac{\left(x+4\right)^2+4}{x+4}=\dfrac{\left(x+2\right)^2+2}{x+2}+\dfrac{\left(x+3\right)^2+3}{x+3}\)
\(\Leftrightarrow x+1+\dfrac{1}{x+1}+x+4+\dfrac{4}{x+4}=x+2+\dfrac{2}{x+2}+x+3+\dfrac{3}{x+3}\)
\(\Leftrightarrow\dfrac{1}{x+1}+\dfrac{4}{x+4}=\dfrac{2}{x+2}+\dfrac{3}{x+3}\)
\(\Leftrightarrow x+5=0\)
hay x=-5
![](https://rs.olm.vn/images/avt/0.png?1311)
`(-(5)/(3))^{3}<x< -(24)/(35).(-5)/(6)`
`->((-5)^{3})/(3^{3})<x< (24.5)/(35.6)`
`->-(125)/(27)<x<(4)/(7)`
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{x-130}{20}\)+\(\dfrac{x-100}{25}\)+\(\dfrac{x-60}{30}\)+\(\dfrac{x-10}{35}\)=10
⇔\(\dfrac{2625\left(x-130\right)}{52500}\)+\(\dfrac{2100\left(x-100\right)}{52500}\)+\(\dfrac{1750\left(x-60\right)}{52500}\)+\(\dfrac{1500\left(x-10\right)}{52500}\)=\(\dfrac{525000}{52500}\)
⇔2625\(x\)-341250+2100\(x\)-210000+1750\(x\)-105000+1500\(x\)-15000=525000
⇔ 7975\(x\) = 1196250
⇔ \(x\) = \(\dfrac{1196250}{7975}\)
⇔\(x \) = 150
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
PT $\Leftrightarrow \frac{x+25}{75}+1+\frac{x+30}{70}+1=\frac{x+35}{65}+1+\frac{x+40}{60}+1$
$\Leftrightarrow \frac{x+100}{75}+\frac{x+100}{70}=\frac{x+100}{65}+\frac{x+100}{60}$
$\Leftrightarrow (x+100)(\frac{1}{75}+\frac{1}{70}-\frac{1}{65}-\frac{1}{60})=0$
Dễ thấy $\frac{1}{75}+\frac{1}{70}-\frac{1}{65}-\frac{1}{60}<0$
$\Rightarrow x+100=0$
$\Leftrightarrow x=-100$ (tm)
![](https://rs.olm.vn/images/avt/0.png?1311)
`[x+35]/1984-[x+30]/1989+[x+19]/2000+[x+23]/[1996=-2`
`<=>[x+35]/1984+1-[x+30]/1989-1+[x+19]/2000+1+[x+23]/1996+1=0`
`<=>[x+2019]/1984-[x+2019]/1989+[x+2019]/2000+[x+2019]/1996=0`
`<=>(x+2019)(1/1984-1/1989+1/2000+1/1996)=0`
`=>x+2019=0`
`<=>x=-2019`
\(\dfrac{x+35}{1984}-\dfrac{x+30}{1989}+\dfrac{x+19}{2000}+\dfrac{x+23}{1996}\text{=}-2\)
\(\Leftrightarrow\dfrac{x+35}{1984}-\dfrac{x+30}{1989}+\dfrac{x+19}{2000}+\dfrac{x+23}{1996}+3-1\text{=}0\)
\(\Leftrightarrow\left(\dfrac{x+35}{1984}+1\right)-\left(\dfrac{x+30}{1989}+1\right)+\left(\dfrac{x+19}{2000}+1\right)+\left(\dfrac{x+23}{1996}+1\right)\text{=}0\)
\(\Leftrightarrow\dfrac{x+2019}{1984}-\dfrac{x+2019}{1989}+\dfrac{x+2019}{2000}+\dfrac{x+2019}{1996}\text{=}0\)
\(\Leftrightarrow\left(x+2019\right)\left(\dfrac{1}{1984}-\dfrac{1}{1989}+\dfrac{1}{2000}+\dfrac{1}{1996}\right)\text{=}0\)
\(\Leftrightarrow\left(x+2019\right)\text{=}0\)
\(\Leftrightarrow x\text{=}-2019\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=\dfrac{4}{3}\cdot\dfrac{9}{8}\cdot\dfrac{16}{15}\cdot\dfrac{25}{24}\cdot\dfrac{36}{35}=\dfrac{12}{7}\)
= 4/3*9/8*16/15*25/24*36/35
=2*2/1*3 * 3*3/2*4 *4*4/3*5 *5*5/4*6 * 6*6/5*7
= (2*3*4*5*6 / 1*2*3*4*5) * ( 2*3*4*5*6 / 3*4*5*6*7)
=6/1* 2/7
= 12/7